2022
DOI: 10.1021/acs.jpcc.1c10067
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Dynamics of Electric Double Layer Formation over Wide Time Scales (10–9–10+5 s) in the Ionic Liquid DEME-TFSI

Abstract: We investigate the transient response of N,N-diethyl-N-(2-methoxyethyl)-N-methylammonium bis­(trifluoromethylsulfonyl)-imide-based ionic liquid (IL) planar capacitors, studying this response over time scales ranging from as little as a few nanoseconds to as much as several days. Our measurements point to the existence of three distinct mechanisms for charging/discharging of the IL. The fastest of these is associated with the development of a standard polarization charge in the bulk of the liquid dielectric, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
(78 reference statements)
2
6
0
Order By: Relevance
“…In Figure S3­(a) in the Supporting Information (SI), we summarize the current–voltage behavior of our device, by carrying out a series of cyclic voltammetric measurements, covering the range of ±0.125 to ±3.0 V under linear voltage ramps that are always completed in 200 s. Therefore, an increase in the voltage range also corresponds to an increase in the sweep rate as well. In Figure S3­(b), the same graph is displayed after normalizing the measured currents, by dividing with the corresponding applied voltage for a better comparison, similar to those reported by Yin et al As can be gathered from the graphs, the electrochemical behavior of our system has a resemblance of a supercapacitor and also indicates the presence of other accompanying electrochemical processes, even as small as a voltage span from −0.125 to +0.125 V. Moreover and as has been already reported by us and others, upon application of even a small voltage bias, the induced current never dies away for time scales ∼10 4 s, as shown in Figure S4. In the cyclic voltammetry experiments, the currents that are scaled by sweep rate clearly increase as the voltage window is expanded, which is an indication of the existence of Faradaic processes.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…In Figure S3­(a) in the Supporting Information (SI), we summarize the current–voltage behavior of our device, by carrying out a series of cyclic voltammetric measurements, covering the range of ±0.125 to ±3.0 V under linear voltage ramps that are always completed in 200 s. Therefore, an increase in the voltage range also corresponds to an increase in the sweep rate as well. In Figure S3­(b), the same graph is displayed after normalizing the measured currents, by dividing with the corresponding applied voltage for a better comparison, similar to those reported by Yin et al As can be gathered from the graphs, the electrochemical behavior of our system has a resemblance of a supercapacitor and also indicates the presence of other accompanying electrochemical processes, even as small as a voltage span from −0.125 to +0.125 V. Moreover and as has been already reported by us and others, upon application of even a small voltage bias, the induced current never dies away for time scales ∼10 4 s, as shown in Figure S4. In the cyclic voltammetry experiments, the currents that are scaled by sweep rate clearly increase as the voltage window is expanded, which is an indication of the existence of Faradaic processes.…”
Section: Resultssupporting
confidence: 78%
“…Very recently, Yin et al have reported on an investigation of a small (1 μm) and IL (DEME-TFSI)-based planar (twoelectrode) capacitor, by recording (in vacuum) its transient current response to a fast-rising, and 0.1−4.0 V pulses, lasting a short duration (100 ms), for capturing a wide time-scale dynamics of the device, and commenting on its fast (micro-tomilliseconds) as well as a very long (10 +5 s) time dependences. 48 Their findings on the extreme long time-scale dynamics are consistent with other previous reports using various physical measurements. 49−57 Researchers working on the use of ILs as electrical doublelayer transistors have also utilized different electrical/electrochemical techniques to tap into the dynamics of ion movements and/or ion transport within such devices in order to understand the intrinsic nature of the EDL charging and possibly establish simple procedures for distinguishing and quantification of electrostatic and electrochemical components.…”
Section: ■ Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, pentacene thin films (5 monolayers (MLs)) were employed to determine the vacuum level shift at the interface between the pentacene thin film and the DEME-TFSI layer. Pentacene and DEME-TFSI were adopted because their basic physical properties have been well-characterized and they are widely utilized as components of devices, such as FETs. , The photoelectron signals from the pentacene thin films were successfully detected even with the DEME-TFSI thickness of 5 nm. By analyzing the PY spectra, we found that the HOMO peak for the pentacene thin films broadens with the coverage of the DEME-TFSI due to the induced energetic disorder on the density of states of the pentacene thin films.…”
Section: Introductionmentioning
confidence: 99%